Perinatal exposure to methoxychlor enhances adult cognitive responses and hippocampal neurogenesis in mice - Martini, Mariangela; Calandreau, Ludovic; Jouhanneau, Mélanie; Mhaouty-Kodja, Sakina; Keller, Matthieu (Frontiers in Behavioral Neuroscience, 2014)
During perinatal life, sex steroids, such as estradiol, have marked effects on the development and function of the nervous system. Environmental estrogens or xenoestrogens are man-made chemicals, which animal and human population encounter in the environment and which are able to disrupt the functioning of the endocrine system. Scientific interest in the effects of exposure to xenoestrogens has focused more on fertility and reproductive behaviors, while the effects on cognitive behaviors have received less attention. Therefore, the present study explored whether the organochlorine insecticide Methoxychlor (MXC), with known xenoestrogens properties, administered during the perinatal period (from gestational day 11 to postnatal day 8) to pregnant-lactating females, at an environmentally relevant dose (20µg/kg (body weight)/day), would also affect learning and memory functions depending on the hippocampus of male and female offspring mice in adulthood. When tested in adulthood, MXC perinatal exposure led to an increase in anxiety-like behavior and in short-term spatial working memory in both sexes. Emotional learning was also assessed using a contextual fear paradigm and MXC treated male and female mice showed an enhanced freezing behavior compared to controls. These results were correlated with an increased survival of adult generated cells in the adult hippocampus. In conclusion, our results show that perinatal exposure to an environmentally relevant dose of MXC has an organizational effect on hippocampus-dependent memory and emotional behaviors.